„Nel banco dove sta il nuntio non vi sedano altri“. Ceremoniál jako forma symbolické komunikace pražského nuncia Antonia Caetaniho (1607-1611) - Tomáš Černušák (Theatrum Historiae)
The diplomatic reports of papal nuncio Antonio Caetani, who worked at the imperial court in Prague in the years 1608–1609, record a few examples relating to a ceremony as a specific form of symbolic communication. Besides ceremonial meetings (incontro) and maintaining a certain sequence in the hierarchy of other diplomats, there are several events reflecting conflict situations in ceremonial practices.